Catheter ablation of atrial fibrillation in women with heart failure with preserved ejection fraction - Maura M. Zylla; Maura M. Zylla; Maura M. Zylla; Johannes Leiner; Johannes Leiner; Johannes Leiner; Ann-Kathrin Rahm; Ann-Kathrin Rahm; Ann-Kathrin Rahm; Tobias Hoffmann; Tobias Hoffmann; Tobias Hoffmann; et al. (Frontiers in Cardiovascular Medicine)
BackgroundHeart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF) often coincide. Female sex is associated with both increased prevalence of HFpEF and reduced therapeutic efficacy of catheter ablation of AF. This sub-analysis of the previously published AFFECT-study evaluates outcome after cryoballoon-ablation in women with and without HFpEF.MethodsOne-hundred-and-two patients (LVEF ≥ 50%) scheduled for cryoballoon-ablation of AF were prospectively enrolled. Forty-two were female. Comprehensive baseline assessment included echocardiography, stress echocardiography, six-minute-walk-test, biomarker- and quality-of-life-assessment (QoL, SF-36), and was repeated at follow-up ≥12 months after AF-ablation. Baseline parameters, procedural characteristics and outcome after AF-ablation were compared between women with and without HFpEF.ResultsWomen with HFpEF (n = 20) were characterized by higher median left atrial volume index (35.8 ml/m2 vs. 25.8 ml/m2, P < 0.001), left ventricular hypertrophy (median left ventricular mass index: 92.0 g/m2 vs. 83.0 g/m2, P = 0.027), reduced distance in the 6-min-walk-test (median: 453 m vs. 527 m, P = 0.008) and higher left atrial pressures (median: 14.0 mmHg vs.9.5 mmHg, P = 0.008) compared to women without HFpEF (n = 21). During follow-up, HFpEF-patients more often experienced AF-related re-hospitalization (36.8% vs. 9.1%, P = 0.039) and numerically higher AF-recurrence-rates (57.9% vs. 31.1%, P = 0.109). There was no significant improvement of heart failure-related symptoms, echocardiographic parameters and cardiac biomarkers levels. QoL showed no significant improvement in both subgroups. Women with HFpEF still exhibited a lower SF-36 Physical Component Summary Score vs. women without HFpEF (median: 41.2 vs. 52.1, P < 0.001).ConclusionWomen with HFpEF constitute a distinct subgroup with high rates of AF-related events after AF-ablation, and persistence of both symptoms and functional hallmarks of HFpEF. Consideration of sex-specific cardiac co-morbidities is crucial for personalization and optimization of AF-therapy.Clinical Trial RegistrationClinicalTrials.gov Identifier NCT05603611.